Parásitos Gastrointestinales en Reptiles en Cautiverio en Lima Metropolitana - Chávez C., Laura (2015)
The aim of the study was to identify gastrointestinal parasites in reptiles kept in captivity in Metropolitan Lima. Reptiles in the Huascar Park (Villa El Salvador) and Sinchi Roca Park (Comas), in the zoo of El Buen Pastor School and in the serpentarium of the Instituto Nacional de Salud were sampled. Stoll samples (n=133) were collected from Chelonoidis denticulata (89), Boa constrictor (11), Iguana iguana (6), Trachemys scripta (3), Bothrops atrox (5), Bothrops barnetti (3), Epicrates cenchria (3), Crotalus durissus terrificus (2) and other nine species. The samples were processed by parasitological diagnostic methods: direct, flotation with zinc sulfate, Ritchie and Ziehl Neelsen staining. Results shown Nyctotherus sp (72/89), Balantidium sp (56/89), Sauricola sp (21/89) in C. denticulate; Alaeuris sp (4/6) and Ozolaimus sp (3/6) in I. iguana; oocysts of Cryptosporidium sp (35/89) in C. denticulate, Rhabdias sp larvae (2/5) in B. atrox and eggs of Porocephalus sp (1/3) in E. cenchria. The results showed that reptiles are carriers of several species of parasites, including some of zoonotic potential.